An unfinished argument: The inclusive non-positivism by Robert Alexy - Carrillo Salgado, Augusto Fernando (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2021)
This work has as a general aim to examine the elements that constitute inclusive non-positivism; an epistemological and philosophical position proposed by Robert Alexy. The methods used are deductive, analytical, and dialectical; the main technique employed has been documentary research. The present document is divided into three sections. First, the elements that constitute Robert Alexy’s inclusive non-positivism are explained. Second, some criticisms formulated to constitutive elements of the inclusive non-positivism are explained according to some ideas of Riccardo Guastini, Juan Antonio García Amado, Joseph Raz, Eugenio Bulygin, Matthias Klatt, Carlos Bernal Pulido, among others. Finally, as a particular objective, a reflection is presented with the purpose of indicating one of the multiple paths that the juridical-scientific studies on the non-inclusive positivism could follow in the future.